KARAKTERISASI ENZIM AMILASE DARI KECAMBAH BIJI JAGUNG KETAN (ZEA MAYS CERATINA L.) - Bahri, Syaiful; Mirzan, Moh.; Hasan, Moh. (Univ. Tadulako, 2012)
The research about characterization of the amylase enzyme from germination glutinous corn seed (Zea mays ceratina L.) was done. The aims of this research is to know the effect of germination time to the activity of the amylase enzyme and characteristics of the amylase enzyme from germination glutinous corn seed (Zea mays ceratina L.). The research was conducted through four phases that is germination stage, extraction, isolation, and characterization. The research device used was Completelly Randomized Design (CRD) and to be continued by BNJ test critical level 5%. Result showed that the germination time that produces the highest activity was 36 hours and the activity of enzyme was 0.0557 sec-1. Isolation of the amylase enzyme purified by salting out method used technical (NH4)2SO4 at concentration 55% with activity of 0.0394 sec-1. The optimum pH was 9, and the activity of enzyme was 0.0207 sec-1. Maximum substrate concentration with the activity 0.0476 sec-1 give at 12.5% (w/v), while the optimum temperature for activity 0.0229 sec-1 was 70 oC. From examination manner analysis for all of free variables results very real effect on the amylase enzyme activity, while the BNJ test critical level of 5% showed a real difference with the other treatments of every variable.